1963
DOI: 10.1136/hrt.25.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Polyuria in Paroxysmal Tachycardia and Paroxysmal Atrial Flutter and Fibrillation

Abstract: When Paul Wood spoke about this to the British Cardiac Society in 1961, we were impressed by the originality of his work on a subject that so many had noticed but failed to investigate. A few months before his death in July 1962, when I asked him if his paper was ready for thejournal, he said that he had not yet been able to get all the evidence he hoped for to establish the full explanation. Unfortunately, he had not the time to complete this. I have, therefore, tried to set out as clearly as possible the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Grossly increased plasma ANP concentrations would not appear to be a distinguishing feature of human essential hypertension. It has long been known that the onset of tachycardia can be associated with a profound natriuresis and diuresis of uncertain cause (Wood, 1963). Preliminary results showed that the onset of tachycardia was associated with very large (up to 140 pmol/1) rises of the plasma ANP concentration in patients who had normal levels (less than 15 pmol/1) immediately before onset, and that these returned rapidly to normal after reversion to sinus rhythm (Anderson et al 19866).…”
Section: Introductionmentioning
confidence: 92%
“…Grossly increased plasma ANP concentrations would not appear to be a distinguishing feature of human essential hypertension. It has long been known that the onset of tachycardia can be associated with a profound natriuresis and diuresis of uncertain cause (Wood, 1963). Preliminary results showed that the onset of tachycardia was associated with very large (up to 140 pmol/1) rises of the plasma ANP concentration in patients who had normal levels (less than 15 pmol/1) immediately before onset, and that these returned rapidly to normal after reversion to sinus rhythm (Anderson et al 19866).…”
Section: Introductionmentioning
confidence: 92%
“…Expansion of the extracellular fluid volume fails to elicit an increase in urine flow when atrial stretch is prevented (2). Conversely, inflation of a balloon within the right atrium, even in the absence of extracellular fluid volume expansion, results in enhanced urine flow and salt excretion (3), and natriuresis and diuresis frequently accompany paroxysmal atrial tachyarrhythmias (4,5). The renal response provoked by atrial distension or atrial tachycardias has usually been ascribed to reflex stimulation of neural stretch receptors located in the subendocardium (6) but a humoral mediator has also been considered (1).…”
Section: Introductionmentioning
confidence: 99%
“…(1986) demonstrated in anaesthetized rabbits that plasma ANP concentration rose with cardiac pacing even after vagal or sympathetic blockade. It has been suggested that atrial distension is the main stimulus for release of ANP in these patients (Schiffrin et al 1985) as pressure in the right atrium increases during paroxysmal supraventricular tachycardia (Wood 1963). Furthermore studies in rats recently suggested that plasma ANP most closely correlates with right atrial pressure (Katsube et al 1985).…”
Section: Discussionmentioning
confidence: 95%